Edukasi tentang Pengolahan dan Manfaat Minyak Sereh bagi Ibu Hamil untuk Persiapan Menyusui di BPM Muzilatul Nisma - Jayanti, Ova; Patriani, Sirly (Universitas Baiturrahim, 2025)
Aromatherapy oil produced from lemongrass plants functions as an antidepressant. It is proven from several studies that lemongrass oil aromatherapy can suppress and relieve stress during pregnancy and prevent postpartum depression during the postpartum period. Indonesia is the world's largest producer of lemongrass. There are 2 types of lemongrass, namely citronella (cymbopogon winterianus) and kitchen lemongrass (cymbopogon flexousus). However, pregnant women do not fully know the benefits of fragrant lemongrass and how to process fragrant lemongrass into lemongrass oil or aromatherapy oil. Therefore, it is necessary to educate pregnant women about the processing and benefits of lemongrass oil for breastfeeding preparation at BPM Muzilatul Nisma. BPM Muzilatul Nisma is a maternity clinic that has implemented complementary therapies in obstetric services, but of the existing complementary therapies, there has never been education related to the processing and utilization of lemongrass oil for pregnant women. This is in line with the needs of most mothers who complain that they cannot breastfeed their babies effectively. Counseling was conducted on July 08, 2023 which was attended by 20 mothers, the time needed for educational activities was ± 1 hour 30 minutes. The first 30 minutes of education about the benefits of lemongrass oil for pregnant women. Education was accompanied by the provision of leaflets to each participant followed by questions and answers. Furthermore, a demonstration on how to process citronella into citronella oil in a simple household-based manner without refining. The demonstration was given in the form of a video. After the education was completed, a posttest was conducted using the same questionnaire as the pretest. It was concluded that there was an increase in knowledge about lemongrass oil, but a low desire to make lemongrass oil independently.